2019
DOI: 10.1093/icc/dtz023
|View full text |Cite
|
Sign up to set email alerts
|

When Linder meets Hirschman: inter-industry linkages and global value chains in business services

Abstract: This article looks at the determinants of a country’s participation in business services (BS) global value chains (GVCs). BS GVCs are comparatively less explored than traditional manufacturing ones, and there is a gap in the literature on the relative positions of countries in BS GVCs and the opportunities they might open for development. This article puts forward and finds empirical support to the conjecture that the domestic structure of backward and forward linkages à la Hirschman, alongside the domestic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 58 publications
(43 reference statements)
2
44
0
1
Order By: Relevance
“…This paper has offered novel empirical evidence to revisit the role of backward and forward linkages à la Hirschman (López-Gonzalez et al 2015, 2019, in a context of NR abundant or dependent emerging countries that face the opportunities and challenges of having to 'diversify away' from NRI. We aim to contribute to the oldage debate on the NR 'curse', which has been recently revamped by further empirical evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper has offered novel empirical evidence to revisit the role of backward and forward linkages à la Hirschman (López-Gonzalez et al 2015, 2019, in a context of NR abundant or dependent emerging countries that face the opportunities and challenges of having to 'diversify away' from NRI. We aim to contribute to the oldage debate on the NR 'curse', which has been recently revamped by further empirical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Building on the Hirschman-Linder Hypothesis put forward in López Gonzáles, Meliciani and Savona (2019) this paper aims to revisit the role of Hirschman linkages, particularly of NR backward-linked business services, to identify whether new patterns of export diversification in NR rich countries can emerge, depending on the revealed comparative advantage in NR of countries, and by distinguishing between extractive industries and agriculture. We aim therefore to contribute to the NR curse debate by offering a novel perspective and empirical evidence that hopefully sparks a whole new set of reflections on how to craft industrial, trade and development policies for NR-rich emerging countries.…”
Section: Introductionmentioning
confidence: 99%
“…Such a role is grounded in their high share of skilled human capital, their contribution to learning processes and knowledge accumulation, and their role as co‐producers of innovation (Gallego and Maroto, ) — for example, by facilitating knowledge transfer coming from foreign firms locating in developing countries. Additionally, an important number of technology‐intensive manufacturing sectors represent a pool of demand for these knowledge‐based business services (Guerrieri and Meliciani, ), which points to the importance of (forward and backward) inter‐industry linkages between business services and the manufacturing sector, and to their use of knowledge and technology (Ciarli et al., ; López‐Gonzalez et al., ; Meliciani and Savona, ). In this respect, a core manufacturing sector may be critical for growth not only per se, but also as it is able to promote the emergence of backward‐ and forward‐linked sectors that Hirschman () would label as ‘high development’ inducive (López‐Gonzalez et al., ), with business services fitting this category.…”
Section: Discussionmentioning
confidence: 99%
“…The region's specialization in export‐oriented manufacturing with strong inter‐industry linkages allows for the development of high‐tech business service sectors which stimulate productivity and growth. The increased tradability of (manufacturing‐linked) business services within GVCs have turned these activities into major players in the current wave of the globalization process (Gallego et al., ), opening up new opportunities for growth in developing economies (Gereffi and Fernandez‐Stark, , ; Hernández et al., ; López‐Gonzalez et al., ). In support of this evidence, some modern tradable services (such as IT‐related services) have notably expanded in Asian countries (for example, India and Philippines) and, as argued by Dasgupta and Singh (), may also lead to the expansion of manufacturing, rather than the other way around.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Fernandez‐Stark, Bamber and Gereffy (2014) hint at the possibility of leveraging on the natural resources endowments in which many LACs abound, to spur diversification in related sophisticated services for export. Elsewhere (Lopez‐Gonzalez, Meliciani and Savona, ) we have empirically shown that participation in business services GVCs is determined by strong forward‐linked, domestic manufacturing industries. Similarly, technological upgrading in agriculture and natural resource industries might need specialised and high value added services, which might join GVCs on more favourable bases, in terms of both governance structure and capabilities accumulation.…”
mentioning
confidence: 90%